The Struts framework : practical guide for Java programmers - Spielman, Sue (Morgan Kaufmann practical guides series., 2003)
Struts is an open-source framework that integrates with standard Java technologies and lets developers build web applications quickly and effectively. In much the same way that Java has overtaken C++, Struts is well poised to become the framework for web application development because of its ability to address the types of issues engineers face when building large-scale web applications. The Struts Framework: Practical Guide for Java Programmers meets the needs of this large audience--estimated today at 2.5 million Java programmers and growing. It provides the systematic exploration required by newcomers as well as the step-by-step instruction for more experienced readers eager to exploit Struts to the fullest. Devoted to the latest version of the framework (v. 1.1) and vividly illustrated with a thorough sample application throughout, this book is an essential resource for all programmers who want to be part of the next stage in the evolution of the web. * Hard-to-find, practical coverage from a highly visible figure in the Java development world. * Among the first books to cover the latest release of Struts, version 1.1. * Reviews all the technologies comprising Struts, including JavaServer Pages, Servlets, XML, Custom Tags, and web and application servers. * Teaches readers the development practices-including design, debugging, internationalization, and implementation-essential to Struts development. * Via a companion web site, provides downloadable sample code and data for use in a Struts-based database application.